Schizophyllum commune Fr. Sebagai Jamur Uji Ketahanan Kayu Standar Nasional Indonesia pada Empat Jenis Kayu Rakyat : Sengon (P. falcataria), Karet (H. brasiliensis), Tusam (P. merkusii), Mangium (A. mangium) - Elis Nina Herliyana; Laila Fithri Maryam; Yusuf Sudo Hadi (Jurnal Silvikultur Tropika, 2011)
Schizophyllum commune Fr. As Indonesian National Standard Wood Resistance Test Fungi on Four Kinds of Community Wood : Sengon, Rubber, Tusam, and MangiumSchizophyllum commune Fr. is a vicious wood decaying fungi that in several cases could cause to 70 % weight loss. These fungi could attack various kind of woods (more than 25 wood species). It has been widely distributed especially in tropical area, and could easily grow in many conditions. This wood decaying fungi has an ability to decompose cell components of the woods through enzymatic processes from a complex to simpler form. Resistance of wood is strongly influenced by the content of extractive substances, although not all of these extractive substances are nocuous to wood destroying organisms. Based on the resistance, most common community woods have a low grade of resistance (grade III, IV, and V). This study aimed to determine the resistance of the four kind community woods which are sengon wood (P. falcataria), rubber (H. brasiliensis), tusam (P. merkusii), and mangium (A. mangium) against S. commune based on SNI 01.7202-2006. Parameters of the wood resistance against S. commune attack could be seen from the sample of weight loss. Based on the results of testing, it was known that sengon wood resistance was classified to a class IV-V (weak to extremely weak resistance to fungal attack) with the weight loss of longitudinal sengon and cross sengon respectively 32.2 and 15.7 %. Rubber wood resistance was classified to a class IV (weak resistance) with the weight loss value of longitudinal rubber and cross rubber respectively 13.8 and 12.0 %. Tusam and mangium wood’s resistance was clasified to a class III (moderate resistance) with the weight loss value of longitudinal tusam and cross tusam respectively 8.0 and 9.3 %. As for the mangium, the weight loss of longitudinal mangium and cross mangium respectively 6.3 and 6.3 %. Thus, the recommended wood as the control for the test of resistance against S.commune attack was sengon wood with the longitudinal direction of fiber. Fungi S. communne could use as the standard and was a recommended fungi for the the resistance test of the wood as it could cause the weight loss up to 3.2 % on sengon wood with the longitudinal direction of fiber.